Respuesta :

[tex]\huge\text{Hey there!}[/tex]

[tex]\huge\textbf{Assuming the equation should be:}[/tex]

[tex]\mathbf{3a - (2^2 + 1)^2 + a}[/tex]

[tex]\huge\textbf{Simplify it: }[/tex]

[tex]\mathbf{3a - (2^2 + 1)^2 + a}[/tex]

[tex]\mathbf{= 3(8) - (2^2 + 1)^2 + 8}[/tex]

[tex]\mathbf{= 24 - (2^2 + 1)^2 + 8}[/tex]

[tex]\mathbf{= 24 - (4 + 1)^2 + 8}[/tex]

[tex]\mathbf{= 24 - 5^2 + 8}[/tex]

[tex]\mathbf{= 24 - 25 + 8}[/tex]

[tex]\mathbf{= -1 + 8}[/tex]

[tex]\mathbf{= 7}[/tex]

[tex]\huge\textbf{Therefore, your answer should be:}[/tex]

[tex]\huge\boxed{\frak{Option\ B. 7}}\huge\checkmark[/tex]

[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]

~[tex]\frak{Amphiitrite1040:)}[/tex]

ACCESS MORE